Panonychus from Georgia: survey, taxonomical status and redescription of P. hadzhibejliae (Reck, 1947) (Acari, Tetranychidae) - Arabuli, Tea; Çobanoglu, Sultan; Auger, Philippe (Zootaxa, 2016)
A survey of Panonychus species was undertaken across Georgia from 2005 to 2014 on various host plants, revealing three species: Panonychus citri (McGregor, 1916), Panonychus hadzhibejliae (Reck, 1947) and Panonychus ulmi (Koch, 1836). New hosts for P. ulmi and P. citri are recorded, Buxus sempervirens, Hedera colchica and Prunus laurocerasus for P. ulmi and Ficus carica for P. citri, whereas P. hadzhibejliae was only found on F. carica. The newly collected material also allowed us to investigate the taxonomical status of P. hadzhibejliae. The comparison of P. hadzhibejliae with the two closely related species sampled in the survey, P. ulmi and P. citri, and with data of P. caricae found in the literature, shows that P. hadzhibejliae is a valid species. It can be separated from the three other Panonychus species without ambiguity especially using the female dorsal setae length in combination with the ratio between the length of the female dorsal opisthosomal f2 and h1 setae and the ratio between the palptarsal terminal eupathidium su and the related solenidion ω. A redescription of P. hadzhibejliae is provided including the male and some morphological characters, measurements and drawings of the female that were omitted in the original description. A key to the world species of Panonychus is also proposed.